Extracellular Vesicles Inhibit Proliferation and Invasion of Ovarian Endometrial Stromal Cells and Their Expression of SF-1, ERβ, and Aromatase - Wang, XiaoQing; Wu, PeiLi; Li, Xin; Zeng, Cheng; Zhu, JingWen; Zhou, YingFang; Lu, Ye; Xue, Qing (Frontiers in Endocrinology, 2021)
Objective: Endometriosis is an estrogen-dependent chronic disease. The abnormal proliferation and invasion of ectopic stromal cells (ESCs) are important manifestations of endometriosis. It is necessary to find safer and more effective treatments. Exosomes derived from human umbilical cord mesenchymal stem cells (UC-MSCs) have been shown to be promising for the treatment of many diseases, except endometriosis. The main purpose of this study is to explore the effect of exosomes derived from UC-MSCs on ESCs, so as to explore the therapeutic value of exosomes on endometriosis. Study design: Following the successful culture and identification of UC-MSCs, we collected the medium of UC-MSCs and extracted exosomes by ultracentrifugation. Then, 120 μg/mL exosomes were used to stimulate ESCs, and ESCs were collected to evaluate cell proliferation, invasion, and expression of estrogen-related proteins(including steroidogenic factor-1(SF-1), estrogen receptors β(ERβ), and aromatase). Results: Compared with the control group treated with isodose phosphate buffered saline(PBS), 120 μg/mL exosomes exposure significantly decreased the expression of cyclinD1 (mRNA: n = 6, P = 0.02; protein: n = 6, P = 0.000) and matrix metalloproteinase (MMP) 9 (mRNA: n = 6, P = 0.04; protein: n = 6, P = 0.000) of ESCs, which were consistent with the results of CCK-8 (n = 6, P < 0.05, from Day2 to Day4) and Transwell experiments(n = 6, P = 0.000). Meanwhile, the expression of SF-1 (encoded by NR5A1, mRNA: n = 6, P = 0.000; protein: n = 6, P = 0.000), ERβ (encoded by ESR2, mRNA: n = 6, P = 0.000; protein: n = 6, P = 0.000) and aromatase (encoded by CYP19A1, mRNA: n = 6, P = 0.04; protein: n = 6, P = 0.000) in ESCs decreased significantly. Conclusion: Taken together, the results show that 120 μg/mL exosomes derived from UC-MSCs can effectively inhibit the proliferation and invasion, as well as the expression of SF-1, ERβ and aromatase of ESCs, thus may leading to the alleviation of endometriosis.